Application of Science Concepts and Disaster Preparedness Capability in Sustainability Learning Oriented by Science Issues Integrated Natural Disaster Mitigation - Elsi Adelia Fitri; Sugiarti Sugiarti; Sulistiawati Sulistiawati; Demi Romawina (IJIS Edu : Indonesian Journal of Integrated Science Education, 2025)
: ESD is a concept that continues to evolve and has received great recognition over the decades. The focus of the ESD  domain is on three things: economy, ecology and society. The role of science education in answering this sustainability issue can be in the form of integrating the issue of sutainability in science content and using sustainability strategies in science education where science education is part of developing ESD. This research aims to design sustainability-oriented learning on integrated science issues of natural disaster mitigation to provide disaster preparedness capabilities for prospective teacher students.  This research method uses a quasi-research experiment involving prospective PGSD teacher students who take the basic concept course of elementary school science, the control class uses the issue of integrated sustainability of floods disaster mitigation, while the experimental class is free from sustainability issues. The disaster preparedness ability of the two classes was explored and analyzed using n-gain and t-test to see the significance of the difference in disaster preparedness ability achieved. The effect size test  was carried out to test  the effect size of the sustainability strategy implemented. The results show that the analysis of the integrated science concept of natural disaster mitigation that can be integrated into  static fluid materials, hydrology, sedimentation, and river siltation, is very relevant to the issue of floods that often occur in the South Sumatra region 2) the results of students' disaster preparedness capabilities show a significant increase or positive impact on natural disaster preparedness.